Real-world study of adverse events associated with gepant use in migraine treatment based on the VigiAccess and U.S. Food and Drug Administration’s adverse event reporting system databases - Liang, Qiaofang; Liao, Xiaolin; Wu, Hongwen; Huang, Yushen; Liang, Taolin; Li, Hailong (Frontiers in Pharmacology, 2024)
Background: This study aimed to investigate the real-world profile of adverse events (AEs) associated with gepant medications in the clinical treatment of migraines by analyzing data collected from the VigiAccess database and the FDA Adverse Event Reporting System (FAERS) database. Nonetheless, comprehensive real-world studies on the safety of gepants are still lacking,Through descriptive statistical analyses, we assessed the incidence and characteristics of AEs, compared AEs among gepants, and uncovered previously unknown AE information, all with the goal of providing a reference for the selection of clinical treatment regimens and AE monitoring. Methods: By extracting all AE reports concerning "rimegepant", "atogepant", and "ubrogepant" from the VigiAccess and FAERSdatabase since its establishment up to March 31, 2024, a retrospective quantitative analysis was conducted. The reporting odds ratio (ROR) method were used to compare AEs among the three gepants. Results: In the VigiAccess and FAERS databases, 23542 AE reports in total, respectively, were identified as being related to gepant medications. Among gastrointestinal system AEs, rimegepant had the greatest proportion and greatest signal strength; nausea was most severe and had the strongest signal in rimegepant AEs, whereas constipation was most prominent and had the strongest signal in atogepant AEs. In skin and subcutaneous tissue disorders, rash and pruritus were more frequently observed with rimegepant, followed by ubrogepant. Alopecia emerged as a novel AE, being more severe in rimegepant and secondarily in atogepant. Regarding cardiac disorders, the three gepants showed comparable rates of cardiac AEs, yet rimegepant exhibited the strongest AE signal. In musculoskeletal and connective tissue AEs, ubrogepant presented the most positive signals for skeletal muscle AEs. Furthermore, among the rare blood and lymphatic system disorder AEs, rimegepant had the highest number of reports of Raynaud's phenomenon and the strongest signal. Conclusion: Gepant medications exhibit similarities and differences in their safety profiles. Analysis of the two databases indicated the presence of AEs across various systems. However, each drug displays distinct incidences and signal intensities for these AEs. These findings suggest that during clinical use, individualized medication selection and AE monitoring should be based on the patient's physiological condition and specific characteristics